A Study on the Optical Properties of Three-Armed Polystyrene and Poly(styrene-b-isobutyl methacrylate) - Kurt, Adnan; Demirelli, Kadir (Wiley, 2010)
Atom transfer radical polymerization (ATRP) of three-armed polystyrene[PS] and poly(styrene-b-isobutyl methacrylate)[PS-b-PiB mu MA] were accomplished using an initiator with tri-active C-Br end group function and cuprous (I) bromide/2,2'-bipyridyne catalytic system. The characterization obtained by FT-IR, H-1-NMR, and GPC techniques. The average molecular weight and polydispersity of PS and PS-b-PiB mu MA were determined as 19,800, 29,300 and as 1.37 and 1.15, respectively, which indicates that the constant concentration of growing chains are present throughout the polymerization. The refractive index and extinction coefficient of the samples were determined in the visible range as a function of wavelength. The refractive index dispersion curves of the thin films were fitted by the Cauchy-Sellmeier model. The width of localized states (E-u) values changed inversely with optical band gaps (E-g) of the films. While the calculated E-u values of films for initiator, PS and PS-b-PiB mu MA were determined as 2.72, 2.98, and 2.94 eV, the E-g values were determined as 3.43; 3.11, and 3.16 eV, respectively. The dispersion parameters of thin films were determined. These parameters changed in the investigated wavelength ranges. POLYM. ENG. SCI., 50:268-277, 2010. (C) 2009 Society of Plastics Engineers
Keywords: Transfer Radical Polymerization; Doped Poly(Methyl Methacrylate); Fluorescent Solar Collector; Electrical-Conductivity; Ethyl-Methacrylate; Copolymers; Films